Covenants, Codes, and Restrictions that Address Environmental Issues in Residential Communities - Mark E. Hostetler (EDIS)
WEC-213, a 7-page fact sheet by Mark E. Hostetler, provides the CCR document for the town of Harmony, Florida, as a model for homeowner’s associations and community planners. The model CCR emphasizes the treatment of wildlife and the management of yards, neighborhoods, and natural areas. Published by the UF Department of Wildlife Ecology and Conservation, August 2006.